2011
DOI: 10.1177/1038411111413217
|View full text |Cite
|
Sign up to set email alerts
|

Work meaning among mid-level professional employees: A study of the importance of work centrality and extrinsic and intrinsic work goals in eight countries

Abstract: We conducted a survey-based study on the meaning of work of some 1500 mid-level professional employees in private and public organizations in eight countries. Using the country clustering described in the GLOBE series of studies and the theoretical framework of the Meaning of Work study, five hypotheses were tested. The study found support for the universal valuation of work and family as major life domains and the relative importance of leisure, religion, and community involvement. Work centrality was related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
3
28
0
4
Order By: Relevance
“…The tool proposed in 1987 by the team is indisputably the most comprehensive tool developed to date for measuring the relationship to work. It is, accordingly, one of the tools that has been most used up till now, be it in part or in full (e.g., Ardichvili, 2005Ardichvili, , 2009Harpaz & Fu, 2002;Isaksson & Johansson, 2000;Kuchinke, Kang, Oh, & Kang, 2008;Manuti, 2006;Peterson & Ruiz-Quintanilla, 2003;Sharabi & Harpaz, 2010 and in highly varied cultural contexts (e.g., Harpaz, Honig, & Coetsier, 2002;Kuchinke et al, 2011;Sharabi, 2011). However, given that occupational and living contexts have changed profoundly since the 1980s, it would seem that the operationalization of certain dimensions would gain from being reconsidered and other items would benefit from being reformulated or created in order to more accurately reflect the present-day reality workers must face.…”
Section: Conceptualizations and Measurements Of The Relationship To Wmentioning
confidence: 99%
See 1 more Smart Citation
“…The tool proposed in 1987 by the team is indisputably the most comprehensive tool developed to date for measuring the relationship to work. It is, accordingly, one of the tools that has been most used up till now, be it in part or in full (e.g., Ardichvili, 2005Ardichvili, , 2009Harpaz & Fu, 2002;Isaksson & Johansson, 2000;Kuchinke, Kang, Oh, & Kang, 2008;Manuti, 2006;Peterson & Ruiz-Quintanilla, 2003;Sharabi & Harpaz, 2010 and in highly varied cultural contexts (e.g., Harpaz, Honig, & Coetsier, 2002;Kuchinke et al, 2011;Sharabi, 2011). However, given that occupational and living contexts have changed profoundly since the 1980s, it would seem that the operationalization of certain dimensions would gain from being reconsidered and other items would benefit from being reformulated or created in order to more accurately reflect the present-day reality workers must face.…”
Section: Conceptualizations and Measurements Of The Relationship To Wmentioning
confidence: 99%
“…Generally, studies tend to show that the higher the value or importance that people attribute to work and the more central it is to their lives, then the more they feel engaged in their role as a worker (Hattrup et al, 2007), the more it is a source of accomplishment, and the more it contributes to their identity and personal development (Arvey, Harpaz, & Liao, 2004;Blustein, 2011;Méda & Vendramin, 2013;Tziner, Ben-David, & Sharoni, 2014). Likewise, numerous studies tend to show that the importance attached to work is a stable dimension in the relationship to work that does not vary greatly throughout a person's lifetime (Ardichvili, 2005;Bal & Kooij, 2010;Harpaz & Fu, 2002;Hirschfeld & Feild, 2000;Kuchinke et al, 2011;Ruiz-Quintanilla, 1991;Samuel & Harpaz, 2004;Saunders & Nedelec, 2014). In the questionnaire, the absolute centrality of work, which is considered to be a stable variable in the relationship to work, was conceptualized using two sub-dimensions, namely: the ideological value of work, defined as the individual's belief in the importance of work in human existence; and the existential value of work, defined as the importance of work in a person's life.…”
Section: Dimension 1: the Absolute Centrality Of Workmentioning
confidence: 99%
“…A good proportion of recent studies on the meaning of work reinforce two MOW dimensions-centrality and valid results, either by elaborating the research hypothesis or by analyzing emerging results. Work centrality is high in almost all researched countries (Belgium, Brazil, China, German, Holland, Hong Kong, Hungary, Israel, Japan, Kazakhstan, Poland, Russia, USA, and Yugoslavia), despite cultural differences among them (Kuchinke, 2009;Kuchinke, Ardichvili, Borchet, & Rozanski, 2009;Kuchinke et al, 2011).…”
Section: Studies On the Meaning Of Workmentioning
confidence: 99%
“…A study by Kuchinke et al (2011) found support for the universal valuation of work and family as major life domains and the relative importance of leisure, religion, and community involvement. Work centrality was related in differentiated ways to performance orientation, assertiveness, and humane orientation indices.…”
Section: Introductionmentioning
confidence: 99%